(3OjhGf GHf GdebQHs - (3Ydj Hf GdebQH Hf efUhQ GdQHYj GdYjhfj, LeGd GdOjf, CHh YHO Gddg,J (B629 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3aEf ef CYXe GdaVGFd GdfajSI, hGdeQGJH GdCfjSI aVjdI OQ GdfXe GdHGQY ce CQLY GdRaQGJ aj CMTGFj hEdGe aj OGQ GdghGf KhGFj s
(3BNQgG (B:s
(3hce fGUM bO YO aj GdfGS NGFfkG hce ZGOQ bO YO aj GdfGS hGajkG s
(3fSNI KGfjIs
(3ade JQO HgG Jdc GdebOeI GdWhjdI GdehLhOI aj GdfSNI GdSGHbIs
(3hQO CjVkG JMJ Qbe (B2202s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs